DUDI-PDCA Curriculum Framework: A Systematic Literature Review of Tourism Vocational Curriculum Development in Indonesian Vocational High Schools (SMK) under the Merdeka Curriculum - Armen; Abdullah, Rijal; Refdinal; Ismi, Riwayatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The relevance of Indonesian Vocational High Schools (SMK) curriculum in the Tourism Service Business (Usaha Layanan Wisata/ULW) concentration a new nomenclature replacing the Tourism Travel Business (UPW) designation under the Merdeka Curriculum remains a critical challenge. With graduate employment rates at 58.3%, systemic competency gaps are evident. No integrative systematic review has examined all three curriculum development stages design, implementation, and evaluation specifically for the ULW concentration. This study: (1) maps ULW curriculum design practices within the link and match framework; (2) identifies critical implementation factors; and (3) examines effective evaluation models. A Systematic Literature Review (SLR) following PRISMA 2020 protocol was conducted across five databases (Scopus, ERIC, SINTA, Garuda, Google Scholar supplementary) for 2014-2024. From 389 identified records, 42 articles met inclusion criteria and were analyzed using thematic synthesis, with inter rater reliability assessed by Cohen's Kappa (κ = 0.81). Findings reveal: (1) ULW curriculum design is dominated by top down approaches with ceremonial industry involvement, producing a 34% competency gap against SKKNI standards; (2) implementation faces structural barriers including teacher industry competency gaps (61.5% without prior industry experience) and largely symbolic teaching factory implementation; and (3) curriculum evaluation remains administrative summative without data driven continuous improvement. Based on this systematic synthesis, this article proposes the DUDI PDCA Curriculum Framework positioning industry partners as active co-developers across all PDCA cycle stages as a grounded conceptual contribution to Indonesian vocational tourism education.